An analysis of selected kinematic variables in national and elite male and female 100-m and 200-m breaststroke swimmers - Thompson, K. G.; Haljand, R.; MacLaren, D. P. (Journal of Sports Sciences, 2000)
The kinematic analysis of competition breaststroke swimming has tended to focus on the mean values of swimming speed, stroke rate and stroke length; values in individual lengths, as well as the start, turns and finish, have largely been ignored. This study includes all such variables and aims to improve the coach's holistic understanding of breaststroke racing by determining the relationships and diff erences between and within these selected kinematic variables. We also compare 100-m events with 200-m events to determine if there are characteristic diff erences between them. Competitive breaststroke swimming performances in 100-m events (males: n = 159, finishing time = 65.05 ± 2.62 s; females: n = 158, finishing time = 74.04 ± 3.66 s) and 200-m events (males: n = 159, finishing time = 141.47 ± 6.15 s; females: n = 158, finishing time = 158.66 ± 7.87 s) were collected and analysed from 12 world, international and national championships. The better 100-m and 200-m breaststroke swimmers were found to demonstrate greater competency in the kinematic variables measured, except stroke kinematics, which were unique to each individual. These findings suggest that coaches should place emphasis on all of the kinematic components in training and that they should attempt to identify the stroke rate to stroke length ratio most appropriate for the individual. Finally, characteristic diff erences do exist between the 100-m and 200-m events, which has implications for how swimmers might train for each event.